Understanding and Solving Late Payment: The Role of Organizational Routines - Maque, Isabelle; San-Jose, Leire (Management international / International Management / Gestiòn Internacional, 2017)
European legislation has so far failed to alleviate late payment. We introduce the concept of organizational routine; this contributes to understanding late payment and its persistence and focuses on more effective ways of alleviating it. The case study between a large Spanish company and its Spanish SME suppliers gives an exemplary illustration of organizational (trade credit) routines and their dynamics in a two-sided business relationship. The large company’s imbalanced routine and the SMEs’ balanced routine explain late payment. Potential for change and the alleviation of late payment is to be found in routines’ internal dynamics and in participants’ understanding.